Produksi Biodiesel dari Dedak Padi dengan Metode In-Situ Dua Tahap Menggunakan Katalis Asam Sulfat dan CaO/Hydrotalcite - Mirzayanti, Yustia Wulandari; Alisa, Ayu; Sari, Devita (Jurnal Rekayasa Mesin, 2020)
In this study, biodiesel is made from rice bran vegetable oil. Biodiesel production was carried out by the in-situ method using two-sides using sulfuric acid catalysts and CaO/hydrotalcite. The solvent used was methanol as an oil component in the material and a reactant in the formation of FAME and n-hexane as a solvent to increase the yield of rice bran oil extraction. CaO/hydrotalcite to the yield of biodiesel produced and composition of biodiesel at the highest yield. As much as 50 grams of rice bran was put into a three-neck flask, then 50 ml of n-hexane were added. Next, 1 ml mixture of a sulfuric acid catalyst and 250 ml of methanol were added. Then, the mixture was reacted at 65Âº. Add stirring to 600 rpm for 90 minutes. Reheating after 90 minutes and a sample of 2.5 grams was taken for FFA testing. Next, the CaO/hydrotalcite catalyst in 10 ml of methanol with a mass variation of 1; 1,5; and 2 grams are added to the reaction flask. The mixture was reacted again at a temperature of 65 ÂºSuitably stirrings 600 rpm for 90 minutes. Based on the BET test results, the CaO/hydrotalcite catalyst surface area was 200.13 m2/g. The best results obtained on CaO/hydrotalcite catalysts were 2 grams with a biodiesel yield of 9.56%. In the highest biodiesel yield, the FAME component is preferred over the oleic acid methyl ester composition with an area of 35.09% at a retention time of 19.14 min.